Listening as an Easy Skill: Analysis of a Particular Context - Morchino, Marcela (International Journal of English Studies, 2009)
In this paper I want to focus on the difficulty perceived by seventh grade students in connection to listening activities in the English class, at some public schools in San Juan, Argentina. This analysis will lead to the examination of contextual factors that might act as unforeseen constraints on the language learning situation.